Penempatan Posisi Transduser Ultrasonik Pada Penampang Pipa untuk Pengukuran Laju Aliran Fluida - Lalu Febrian Wiranata; I Wayan Raka Ardana (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2022)
Fluid flow rate measurement is important in industries, especially determining fluid flow rate. This process requires a good level of precision and accuracy because it refers to each volumetric's price or custody transfer processor. Many devices are used to measure flow rates, but from some devices, ultrasonic flowmeters are considered, which have more advantages than others. Ultrasonic flowmeters also have some problems, especially in installation, so this research aims to simulate the position of path configuration. The method refers to the weighting process of multi-path configuration and the simulation of track performance, which includes three-factor, hydrodynamic (H), orientation sensitivity (S) and orientation range (T). Each trajectory pattern is rotated 1ᴼ at each angle. In addition, there are also parameter functions that are used to image the profile. The test uses 7 path configurations, so an ideal form is obtained to be implemented. After multiplying weighting factors, the obtained value of hydrodynamic (H) for Area weighting method (1.002), the best value 1. Orientation sensitivity (S), with Area weighting method (0.019), the best result is 0. Meanwhile, with orientation range (T) 1%, with Area weighting method (163,2), the best value is 180.